Struggling writers in elementary school: Capturing drivers of performance. (April 2019) - Dockrell, Julie E.; Connelly, Vincent; Arfè, Barbara
Abstract: Conceptualising the difficulties experienced by struggling writers in middle elementary school is of both theoretical and practical importance. To further our understanding of the problems experienced by struggling writers we aimed to identify the writing measure which best discriminated struggling writers from their peers, and the proximal and distal factors which contributed to performance. The performance of 96 students (Mean age 10; 4), 39 of whom were independently identified as struggling writers using a norm referenced standardised test, was examined at word, sentence, and text level. Standardised measures of transcription, oral language and working memory were collected. The extent to which independent product and process writing measures accurately identified the students was tested using ROC analyses. The skills which underpinned performance were examined using regression analyses and path analysis. Written sentence generation was the most sensitive and specific measure to identify struggling writers at this point in development and, was concurrently predicted by both oral sentence level skills, handwriting fluency and listening span. Path models demonstrated that oral language contributed both directly and indirectly to sentence level writing. Implications for developmental models of writing and support for struggling writers are discussed. Highlights: Writing product and process measures were used to capture struggling writers. Struggling writers were identified by their written sentence generation performance. Transcription contributed directly to sentence generation. Oral sentence skills contributed directly and indirectly to sentence generation.